New Product Diffusion: Evidence from light quadricycle purchases in Finland - Rauhamäki, Joona (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
The purpose of this study is to explore whether social influence has a temporal and spatial effect on the adaptation of new product? In general, the increased amount of data organizations have at their disposal has forced these organizations to develop and adapt new techniques in order to utilize this torrent of new information. This new onslaught of data is known as big data. The study relies on open data, a concept related to big data. Open data sets, or data which is gathered by public organizations, and which is made available without any restrictions on its usage or distribution, are utilized in the empirical part. To shed light on how new products spread, the study utilizes the theory of diffusion. Diffusion is a process of communicating an innovation through specific channels over time among members of a social system. The empirical part of the study was conducted as a quantitative statistical research on panel data. The empirical data set of the study has been extracted from three data sets. The goal of the study is to examine the marginal influence of neighborhood purchases of light quadricycles to the propensity of the subject to buy a light quadricycle. The analysis was conducted by using multiple logistic regressions. The analysis finds support for most of the hypotheses. For the whole sample, previous purchases in the same area within the last year has a positive effect on the propensity to purchase. The purchases are relatively more prevalent in suburban and rural areas when compared to urban areas. The study also found strong support for new vehicles triggering more purchases of new, as opposed to used, vehicles. Additionally, purchases of a specific brand of vehicle have a positive effect on latter purchases of the same brand.